Short communication. Price determinants of Chilean wines in the US market: a hedonic approach - Troncoso, J.L.=700 1 Aguirre, M.
(Es, En)
ilus., 16 ref.
Keywords: VINOS; PRECIOS; CALIDAD; MADURAMIENTO; CHILE